Orientacja procesowa w różnych koncepcjach i modelach referencyjnych zarządzania łańcuchem dostaw - Witkowski, Jarosław (Process Orientation in Different Supply Chain Management Concepts and Reference Models, 2009)
The paper deals with comparative analyses of the processes in the most popular SCM concepts and models, such as: Supply Chain Operations Reference (SCOR model) created by Supply Chain Council (SCC), reference model created by Global Supply Chain Forum (GSCF model) as well as Seuring and Goldbach product-relationship matrix. In spite of the differences between the described models all of them can be considered as effective management tools for measuring and evaluating supply chain processes.(original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 52, s. 136-143